PROPAGAÇÃO VEGETATIVA DE ESPÉCIES FLORESTAIS DA MATA ATLÂNTICA - Sant'Ana, Bruna Tomaz (2021)
Vegetative propagation has the potential to be used in native forest species, especially for those that have difficulties in propagating seeds, and can be used for commercial purposes, as well as assisting in the rescue and conservation of forest genetic resources. The aim of this study was to study the vegetative propagation of three forest species native to the Atlantic Forest. The experiments were carried out at the Department of Forestry and Wood Sciences of the Center for Agricultural Sciences and Engineering to the Federal University of Espírito Santo, Jerônimo Monteiro-ES. The thesis was structured in three chapters. In chapter 1, mini-cutting was studied for the species of jequitibá-rosa, evaluating the influence of nitrogen doses on the productivity of the mini-stumps and the rooting of mini-cuttings. For this, five nitrogen doses (0, 50, 100, 200 and 400 mg L-1 ) were tested in the mini-stumps, with five replications, in a completely randomized design. For rooting, a completely randomized design was adopted, in a 2x5 factorial scheme, that is, two types of minicuttings (apical and intermediate) and five doses of nitrogen from the ministumps (0, 50, 100, 200 and 400 mg L-1 ). The application of the 200 mg L-1 dose of nitrogen showed significant effects on the rooting of the jequitibá rosa by mini-cutting. In chapter 2, the species studied was Paratecoma peroba, and the aim was to evaluate the response of the production of viable sprouting for the production of minicuttings, subjecting the mini-stumps to two factors: pruning and controlled release fertilizer. The experiment was carried out in a completely randomized design, in a 3x5 factorial scheme, with three pruning heights x five doses of CRF (0, 2, 4, 6 and 8 kg m-3 ). Sprouting induction through pruning was effective for invigorating mini-stumps; more sprouts are being produced when subjected to stripping at a height of 20 cm, recommending a height of 20 cm for the production and rooting of mini cuttings of Paratecoma peroba. In chapter 3, the vegetative propagation of the species Lecythis pisonis was studied. For this, the influence of the age of the seedlings (30, 60 and 90 days) on the rooting of mini-cuttings from the apex of the seedlings was evaluated. The age of the seedlings influenced the rooting, and the highest percentage was obtained from seedlings aged 30 days. The presence of a differentiated sheath in the periderm, possibly constitutes an anatomical barrier in Lecythis pisonis.